Lipid profile in relation to inflammatory and insulin resistance markers and anthropometric indices in the apparently healthy abdominally obese - Naghizadeh, Mahsa; Saghafi-Asl, Maryam; Amiri, Parichehr; Karamzad, Nahid (Progress in Nutrition, 2019)
Background: The present study aimed to investigate the association of lipid profile with anthropometric indices, Insulin resistance (IR), and inflammatory markers in apparently healthy abdominally obese persons, subdivided into insulin-resistant and non-insulin-resistant groups. Methods: In this cross-sectional study, 86 apparently healthy abdominally obese subjects were recruited, and divided into two groups based on their IR. Fasting blood samples were collected to determine serum metabolic features, and inflammatory markers (free fatty acids, lipopolysaccharide binding protein (LBP), interferon β, and Interleukin 1β). Abdominal obesity was defined as having waist circumference (WC)≥95cm. Anthropometric indices including BMI, WC, and WHR were assessed. Results: WC (p=0.020), Waist to hip ratio (p=0.010), HDL-C (p=0.005), and LDL-C (p=0.002) were significantly different between the two groups. WHR was significantly correlated with HDL-C (r=-0.315; p=0.002). There were significant differences in fasting insulin, HOMA-IR, and QUICKI (p<0.001 for all) between the IR and NIR groups. HOMA-IR was correlated with HDL-C (r=-0.25; p=0.019). Also, there was a significant correlation between QUICKI and FBS (r=-0.266; p=0.012). Other than serum LBP (p=0.038), there was no significant difference in inflammatory markers between the two groups. However, all inflammatory markers were significantly correlated with each other. Conclusion: This research demonstrates that WC, WHR, LDL-C, and LBP are higher and HDL-C is lower in the insulin resistant abdominally obese than non-insulin resistant abdominally obese. HOMA-IR was correlated with WC. There was a significant correlation of QUICKI with WC and HDL-C in the apparently healthy abdominally obese.